A Computational Study on the Effects of Molecular Structures of Di-n-butyldithiophosphate and of its Derivatives on the Stability of Their Complex Compounds with Rare-Earth Elements - Nurdeni Nurdeni; Atje Setiawan Abdullah; Budi Nurani Ruchjana; Hardianto A; Anggraeni A; Muthalib A; Husein H Bahti (Jurnal Kimia Valensi, 2019)
The stability of complex compounds  formed from the ligand di-n-butyldithiophosphate (DBDTP) and its derivatives, with ions of rare-earth elements (REEs), such as gadolinium ion (Gd3+), is an important factor in the separation and purification processes of the elements using solvent extraction method. The complex stability is dependent, one of which, on the partial charge of the donor atom (S atom in this case) in the molecule of DBDTP or its derivatives. The more negative the partial charge of the donor atom, the more stable is the complex compound formed. The purpose of this study is to explore the effect of electron donating, and of electron withdrawing groups, as well as the effect of the structure of the butyl group in the molecules of  DBDTP and or its derivatives on the partial charge of the donor atom. The method used was the semi empirical quantum mechanical calculations, i.e. the Austin Model 1 (AM1). The results of the study showed that the electron withdrawing group of -CN had resulted in the most positive charge on the donor atom, if it is on the second carbon atom of the butyl group in the DBDTP and or its derivatives. Conversely, in the same carbon atom position, the donating electron group of -CH=CH2 had generated the most negative partial charge on the donor atom. Furthermore, the results of this study also revealed that the sec-butyl isomer produced the most negative partial charge on the donor atom, among other isomers.